2020
DOI: 10.1002/bmc.4940
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the therapeutic effect of Shaoyao Gancao decoction on CCL4‐induced liver injury in rats by metabolomic analysis

Abstract: Shaoyao Gancao decoction (SGD) is a famous Chinese traditional prescription for treating liver injury. In this research, we investigated the therapeutic effects of SGD on liver injury and its metabolic mechanisms using 1 H NMR and UPLC-MS. Serum biochemical indicators and histopathological methods were used to determine the mechanism of action of SGD in treating liver injury. An orthogonal partial least squares discriminant analysis method was used to screen potential metabolic markers, and the MetaboAnalyst a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…LPC is derived from fatty acids through phospholipid metabolism, has the function of inducing inflammation and participates in autoimmune regulation (Fuchs, Schiller, Wagner, Häntzschel, & Arnold, 2005;Wang et al, 2016). An increase in LPC was found in rats with carbon tetrachloride-mediated liver injury (Sun et al, 2020). CHDJ might cause inflammation and liver damage in vivo.…”
Section: Lipid Metabolismmentioning
confidence: 87%
“…LPC is derived from fatty acids through phospholipid metabolism, has the function of inducing inflammation and participates in autoimmune regulation (Fuchs, Schiller, Wagner, Häntzschel, & Arnold, 2005;Wang et al, 2016). An increase in LPC was found in rats with carbon tetrachloride-mediated liver injury (Sun et al, 2020). CHDJ might cause inflammation and liver damage in vivo.…”
Section: Lipid Metabolismmentioning
confidence: 87%
“…Con was given the same amount of soybean oil. From the third week, SGDT and PSGDT were given SGD (1.5 g/kg) orally once a day ( Sun et al, 2020b ). At the same time, PLIM and PSGDT were given antibiotics (twice a day for 3 days before administration and once a day after administration).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis by 1 H NMR was as previously described ( Sun et al, 2020b ). Briefly, spectra were acquired on Bruker AV 600 MHz superconducting Fourier transform NMR spectrometer (Bruker, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study found that SGD had an obvious liver-protecting effect [ 15 ]. After 14 days of oral administration of SGD in model group rats, the serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total bilirubin (TBIL) were significantly decreased, and the histopathological structure of the liver was significantly improved.…”
Section: Introductionmentioning
confidence: 99%